Lung fibrosis and exposure to wood dusts: Two cases report and review of the literature - Matteo Riccò (Nofer Institute of Occupational Medicine, 2015)
Introduction: Increasing evidence suggests that idiopathic pulmonary fibrosis (IPF) occurs more often in subjects previously exposed to wood dusts than in non-exposed subjects. Here we report 2 cases of the IPF among workers prolongedly exposed to high levels of hardwood dusts. Case report: The case No. 1: An 83 year-old male former smoker, retired joiner developed mild dyspnoea and chronic dry cough over the period preceding the examination. Pulmonary function tests (PFT) identified a mild restrictive pattern and diffusion capacity for carbon dioxide (CO2) that was severely impaired (57% of predicted value). High resolution computer tomography (HRCT) identified bilateral, subpleural basal reticular opacities in honeycombing, without any nodules or ground-glass opacities. The case No. 2: A 73 year-old male retired joiner, never smoker, presented a 3-year history of progressive breathlessness and non-productive cough in mild hypoxemia. Pulmonary function tests suggested a moderate restrictive pattern in severely impaired diffusion capacity for CO2 (54% of predicted value). High resolution computer tomography identified diffuse peripheral reticular opacities and honeycombing of lower fields, with apico-basilar gradient. Both cases received diagnosis of the idiopathic pulmonary fibrosis. Discussion: The pulmonary fibrosis is a common feature of several diseases and may be induced by inflammatory disorders following inhalation of organic and inorganic dusts (e.g., asbestos, silica), and several reports suggest that many cases of the IPF may be in fact secondary to occupational dust exposure as in the case reports we present here. Conclusions: Occupational exposure to wood dusts may be a risk factor for the IPF. Unfortunately, exposure reconstruction is frequently inconsistent and anamnesis often misses other causes of the pulmonary fibrosis (e.g., extrinsic allergic alveolitis). Med Pr 2015;66(5):739-747